The Effect of Educational Design Thinking In Interest In Entrepreneurship - Farid, Ahmad Ibnu Mihsan; Riswandi, Riswandi; Nurfitriya, Mira (A Social Science and Entrepreneurship Journal, 2024)
Design thinking inside the field of education is used as one way that can help teachers and students in measuring a problem and finding possible alternative solutions. This study aims to determine how much influence Design education has on the interest in entrepreneurship at SMAN 1 Simpenan, this research uses Quantitative method and includes the type of causal associative research. The population of this study are students of class XII Social SMAN 1 Simpenan who have already implemented entrepreneurship learning. Sampling in research using techniques saturated sampling of 46 students. Data collection techniques using techniques observation, documentation and questionnaires. The analysis technique uses the assumption test, namely test normality, linearity test, and hypothesis testing using simple linear regression and using the t test to look for significance.